The Real Effects of Financial Markets: The Impact of Prices on Takeovers - EDMANS, ALEX; GOLDSTEIN, ITAY; JIANG, WEI (Journal of Finance, 2012)
ABSTRACT Using mutual fund redemptions as an instrument for price changes, we identify a strong effect of market prices on takeover activity (the “trigger effect”). An interquartile decrease in valuation leads to a seven percentage point increase in acquisition likelihood, relative to a 6% unconditional takeover probability. Instrumentation addresses the fact that prices are endogenous and increase in anticipation of a takeover (the “anticipation effect”). Our results overturn prior literature that finds a weak relation between prices and takeovers without instrumentation. These findings imply that financial markets have real effects: They impose discipline on managers by triggering takeover threats.